A contribution to the knowledge of Sweltsa exquisita (Frison) and S. occidens (Frison) and description of a new species of Sweltsa from the northern Rocky Mountains, U.S.A. (Plecoptera: Chloroperlidae) - Kondratieff, Boris C. (Illiesia, 2009)
The fine detail of the male epiproct and aedeagus of two species of similar habitus of Western Nearctic Sweltsa, S. exquisita (Frison) and S. occidens (Frison) are illustrated using the scanning electron microscope. A new speciesrelated to S. occidens, S. durfeei sp. n., is described from Montana and Idaho. Electron micrographs of the female subgenital plate are provided ofS. equisita and S. durfeei sp. n. for comparison.
Keywords: Chloroperlidae; entomology; new species; Sweltsa; United States of America; USA; Plecoptera; Rocky Mountains